Fueling the engine: induction of AMP-activated protein kinase in trout skeletal muscle by swimming - Magnoni, Leonardo Julián (2014)
AMP-activated protein kinase (AMPK) is well known to be induced by exercise and to mediate important metabolic changes in the skeletal muscle of mammals. Despite the physiological importance of exercise as a modulator of energy use by locomotory muscle, the regulation of this enzyme by swimming has not been investigated in fish. We found that sustained swimming (40 days at 0.75 body lengths s−1) increased AMPK activity in red and white trout skeletal muscle (3.9- and 2.2-fold, respectively) as well as the expression of AMPK target genes involved in energy use: lipoprotein lipase and citrate synthase in red and white muscle and CPT1β1b and PGC-1α in red muscle. Furthermore, electrical pulse stimulation of cultured trout myotubes increased AMPK activity and glucose uptake (1.9- and 1.2-fold, respectively) in an AMPK-dependent manner. These results suggest that AMPK may play an important mediatory role in the metabolic adaptation to swimming in fish skeletal muscle.